The Architecture of Collapse: The Global System in the 21st Century - de Miguel Rodríguez, José Manuel (Revista Española de Investigaciones Sociológicas, 2024)
The Architecture of Collapse: The Global System in the 21st Century Mauro F. Guillén Oxford University Press, 2015